Financial Feasibility and Sensitivity Analysis of Smallholder Dairy Farming in Temeke, Tanzania - Tillya, Luciana; Relawati, Rahayu (HABITAT, 2026)
Purpose: Dairy farming contributes to food security, income generation and employment to smallholder dairy farmers in Temeke, yet its financial viability under real market conditions remain insufficiently documented. Design/Methodology/Approach: A case study design was employed, using primary data that was collected through structured questionnaire administered to the purposively selected five representative smallholder dairy farms between October and November 2025 in Temeke District, Tanzania. Investment cost, operating expenses and revenue streams were gathered and analyzed using Investment Appraisal criteria including Net Present Value, Gross and Net Benefit ratio, Internal Rate of Return and Payback Period over seven years project life at 8% discount rate. Findings: The study results revealed that smallholder dairy farming is economically viable, the positive NPV indicates that future discounted returns substantially exceed the investment capital, the Gross B/C ratio greater than 1 explains that gross revenues is more than total costs, and the Net B/C ratio confirms that net benefits outweigh net costs. The IRR of 25.78% substantially exceeds the 8% discount rate, indicating that the project generates returns well above the cost of capital, while a Payback Period of less than two years significantly reduces investment risk for capital-constrained smallholders. Sensitivity analysis reveals that revenue is the dominant risk factor. Originality/Value/Novelty: The study provides comprehensive multi criteria investment appraisal combined with sensitivity analysis for peri-urban smallholder dairy systems in Tanzania establishing achievable economic standards. The study findings offer guidance for farmers planning for dairy investment, for policymakers in developing input support programs against price volatility and for financial institutions designing financial solutions suited to sector’s risk profile.